The black rose - Costain, Thomas B. 1885-1965 (Doubleday, Doran & Co, 1945)
Walter of Gurnie, bastard son of an English peer, is forced to flee from Oxford for his part in the university riots of 1273. Inspired by Friar Bacon, he determines to travel to China. With his friend Tristam, he fights his way to the heart of the fabulous Mongol Empire, and returns famous, to find that he must choose between the first love he thought lost and the exotic flower that he found in the East.